"Peace and reconciliation." A constant and completed message - Bilbao Alberdi, Galo (Razón y fe, 2018)
These pages try to analyze the ecclesial discourse, especially that of the bishops, on the victims of terrorism. Even if the bishops were conditioned for more than thirty years by the ambient climate and were not always up to the task, they have, for a long time, made the pain of the victims their own and have vindicated for them and with them their rights to the truth, justice and memory. Permanently insisting on solidarity and reconciliation, although not sufficiently elaborated and specified.